(untitled) (Contemporary Mathematics, 2025)
The paper addresses the latest form of Boussinesq equation with generalized form of cubic nonlinearity. The solitary waves are recovered from the model using traveling wave hypothesis. The conservation laws are recovered from the model. The conservation laws are obtained using the method of multipliers. Finally, the complete discriminant method yields shock waves and cnoidal waves as well. The numerical simulations supplement the analytical results.